SURVIVAL STRATEGY IN JOBS PORTRAYED IN DAVID FRANKEL’S THE DEVIL WEARS PRADA: A PSYCHOANALYTIC PERSPECTIVE - Fasya, Syahdina Alifia; Thoyibi, M. (Journal of Language and Literature, 2023)
The aim of this study is to analyze the survival strategy in jobs in the characters David Frankel’s The Devil Wears Prada movie. This study uses Alfred Adler’s individual psychological theory to describe the characters in the movie. This research used a descriptive qualitative method. In this research there are two types of the data, namely primary and secondary data. The primary data is collected from word, picture, and audio from the character to describe the survival strategy. The secondary data of this research is from journals and articles that related with this research. The conclusion of this study is, firstly, five indicators of survival strategy in jobs there is career path, employee benefits, fighting for position, aggressive behavior, and nice behavior. Secondly, the depiction is divided into characters, setting, and events. Lastly, the reason why David Frankel addressed survival strategy because Frankel wants other to see the survival strategy in a person especially in the field of work.